THE CASPIAN AND THE CAUCASUS IN RUSSIA’S GEOPOLITICAL INTERESTS: HISTORICAL ASPECTS - GASANOV, Magomed (CENTRAL ASIA AND THE CAUCASUS, 2005)
The Caspian-Caucasian region has acquired a special geopolitical importance: in the past ten years no other region has attracted as much attention as the Caucasus because of the transportation lines that connect Europe and Asia and the shortest West-bound route for Caspian oil, the reserves of which are second only to the oil wealth of the Middle East. Its territory can be used as a strategic toehold for influencing its neighbors—Turkey, Iran, the Central Asian countries, and China.1 This multiethnic region has developed into the epicenter of historic events and processes caused by the clash of local and global interests: Russia, the United States, some of the West European countries, as well as Iran and Turkey have turned their attention to the Caucasus. The Caspian, which is described as “the traditional zone of Russia’s national interests,” has become even more important. The Foreign Policy Conception of the Russian Federation adopted in 2000 says: “Russia will insist on a status for the Caspian Sea which will allow the coastal states to cooperate on a mutually advantageous and just basis in using the region’s resources taking due account of the legal interests of all of them.” 2 The part that belongs to the Russian Federation is its southernmost border territory used for economic and other contacts with the trans-Caucasus and with certain other countries across the Caspian Sea with its ice-free ports. Today Russia and Iran border on new independent states on the Caspian shores—Azerbaijan, Kazakhstan, and Turkmenistan—while Russia’s presence there and in the Caucasus is shrinking CENTRAL ASIA AND THE CAUCASUS under American pressure and the influence of Turkey, Iran, European states, the APR, and Middle East countries. For many centuries Russia has been fighting to establish its influence in the Caspian Sea and drive away all other powers wishing to do the same.